Tactics of involvement of the specialist to carrying out a search - Яремчук, В. О. (Theory and practice of jurisprudence, 2016)
It is analysed actual problems of tactics of involvement of the specialist to carrying out a search. Features of participation of the specialist in realization of tactical receptions of a search are investigated. Features of involvement of the specialist to search planning, participation of group of specialists in carrying out a search are designated.